The high season : a novel - Blundell, Judy (Random House, 2018)
"The ultimate summer read--featuring indelible characters, crackling wit, and sophisticated storytelling--about one season when everything in a woman's life goes wrong. On Memorial Day weekend in a seaside town on Long Island, Ruthie, her still-adored ex-husband, Mike, and the couple's sullen fifteen-year-old daughter, Jem, are packing up the last bits of their household in preparation for the yearly arrival of a wealthy renter from Manhattan. It is what Jem calls "the summer bummer"; her parents own a beautiful house that they have renovated by hand from top to bottom, but which they can only afford to keep by leasing it out during the best part of the year. Soon Ruthie's relationship with Mike seems about to disappear for good. The job she loves, as the underpaid and undervalued director of the local arts museum, is under siege from a coterie of rich women from the city, who want to use it as an opportunity for social climbing. An old flame who once broke her heart and betrayed her is back on the scene, causing Ruthie to re-evaluate their romance. And in the midst of it all, her teenage daughter Jem could be involved in a dangerous and destructive relationship of her own. This is a novel about the dreams and ambitions of youth coming to terms with the realities of middle-age; about the way desperation can make us astonish ourselves; and about how the most disruptive events in our lives can sometimes twist endings into new beginnings"--